Institutional ownership and investment efficiency: Evidence from Iran - Mohammad Moradi; Hassan Yazdifar; Hoda Eskandar; Navid Reza Namazi (Journal of Risk and Financial Management, 2022)
Investment efficiency shows how well a company invests its assets. Although institutional shareholders play undeniable roles in companies, it is not clear whether they are able to monitor managers and make investment decisions or not. This study gives answers to stakeholders, addresses concerns about the effect of the owners on investment efficiency, and aims to add to the literature on emerging markets by investigating the relationship in Iran, a different environment from developed ones. Based on monitoring power, the shareholders are divided into two types: active and passive ones. Investment problems are classified into two types: over- and under-investment problems. The sample consists of 101 firms listed on the Tehran Stock Exchange between 2010 and 2016. Some regression models are used. The results illustrated that institutional owners have a positive effect on investment efficiency and decrease both over- and under-investment problems and so, the efficient monitoring school is approved. Additionally, active ones are positively correlated with investment efficiency and decrease both investment inefficiency problems. Institutional ownership is the cause of investment efficiency, not the reverse. Based on findings, in emerging markets like Iran's market, investors are recommended to give notice to the level of active ownership in firms; ownership structure is a good sign of efficiency.
Keywords: 650; active institutional owners; investment inefficiency problems; over-investment; under-investment